Ditando moda: análise do desempenho do Arranjo Produtivo Local da indústria do vestuário em Espinosa – MG - Délcio Pereira Fortes (2020)
This dissertation’s general objective is investigating the Local Productive Arrangement of Clothing in the Town of Espinosa – Minas Gerais State, its organization’s way, its level of maturity, its main subjects and local governance structure, analyzing its economic impact in the region. Espinosa, the arrangement’s fulcrum, is a small town located in the extreme north of Minas Gerais State, geographically distant from the major industrial and commercial centers in the country, without showy tourist and cultural appeals. The dissertation has been built from the perspective of endogenous development, the agglomerations of companies and the function of innovation, cooperation and creativity in the economic growth’s theories. The study is qualitative, quantitative and descriptive. The instruments of data collection were bibliographic and documentary survey, direct observation and interviews, using semi-structured questionnaires, with the managers of the confections, factions, businessmen, leaders and people responsible for the support organizations that compose the Local Productive Arrangement governance. The diagnosis carried out by field, combined with general information about the clothing segment in Brazil and in the world, allowed to characterize the arrangement’s type, the role of the anchor company, the production process, the level of competitiveness, the form of governance, the associated public policies, the opportunities and threats that permeate this Local Productive Arrangement. The study shows that Local Productive Arrangement of Clothing in Espinosa has significant relevance in the region's economy, in attracting and maintaining related companies, in generating jobs, innovations and average remuneration for the town.